Pregnant women's eHealth literacy and attitudes toward internet health information and their relationship to shared decision making: a cross-sectional study. - Minju Kim; Gungeong Lee (Women's Health Nursing, 2025)
Purpose: This study investigated eHealth literacy and attitudes toward internet health information among pregnant women and analyzed the associations between these factors and shared decision-making related to pregnancy and birth. Methods The participants were 130 pregnant women receiving care at an obstetrics and gynecology department of a tertiary general hospital in Seoul, Korea. Data on eHealth literacy, attitudes toward internet health information, and shared decision-making were collected via an online survey conducted in October 2024. The collected data were analyzed using frequency analysis, descriptive statistics, Pearson correlation coefficients, the independent t-test, one-way analysis of variance, and hierarchical multiple regression. Results: The mean age ofparticipants was 31.73±2.86 years. Thirty percent of the participants were in early pregnancy, 37.7% in mid-pregnancy, and 32.3% in late pregnancy. The mean eHealth literacy score was 4.11±0.75, indicating a high level. The average score for attitudes toward internet health information was 4.10±0.73, reflecting positive attitudes. The mean score for shared decision-making was also high, at 4.17±0.73. Higher eHealth literacy and more positive attitudes toward internet health information were found to significantly influence shared decision-making (F=41.03, p<.001), explaining 46.3% of the variance. Conclusioi A high level of eHealth literacy and positive attitudes toward internet health information are important for promoting shared decision-making among pregnant women. Public institutions should offer educational programs that improve the ability to search for and utilize health information. In clinical settings, specialized counselors should be employed to provide personalized education and accurate information supporting informed maternal health decisions.